Analysis and evaluation of challenges in the integration of Industry 4.0 and sustainable steel reverse logistics network. (January 2022) - Pourmehdi, Mohammad; Paydar, Mohammad Mahdi; Ghadimi, Pezhman; Azadnia, Amir Hossein
Graphical abstract: Highlights: Twenty-one challenges for sustainable integration of I4.0 and RL were identified. The interrelation of challenges was determined through ISM. The rank of challenges regarding their interrelation was determined by FANP. Experts assisting in ISM and FANP were chosen based on some qualification criteria. The problem was solved based on a real case in a developing country. Abstract: Industry 4.0 (I4.0) is a comparatively new phenomenon, and it is most probable that developing countries would face challenges in adapting it for improving the processes of supply chains and moving toward sustainability. The steel industry is the core of industrial growth, and it has an indispensable role in the development of countries. Steel is a highly recyclable product, meaning that it can be reused infinitely, increasing the significance of its reverse logistics. Although many studies have been conducted in the area of I4.0 and supply chain management, less attention has been devoted to finding and analyzing potential challenges of I4.0 technologies integration in steel reverse logistics activities. Therefore, this study is conducted to identify and analyse the challenges to efficient integration of I4.0 and sustainable steel reverse logistics system. Data collection is conducted with the assistance of qualified experts familiar with the steel supply chain and I4.0 concept. The interrelations of challenges are specified by Interpretive Structural Modeling, and the final ranking of challenges is determined through the Fuzzy Analytical Network Process. After validating the completed questionnaires, the absence of experts in I4.0, lack of clear comprehension of I4.0 concepts, training programs, and governmental policies and support are determined as the most critical challenges. Finally, the results and discussion, which can help practitioners in the efficient adoption of I4.0 to have a sustainable reverse logistics system, are presented.